Anti-glomerular basement membrane disease associated with thin basement membrane nephropathy: A case report. Issue 20 (21st May 2021) - Jung, Chi Young; Lee, Sun-Jae; Kim, Min-Kyung; Ahn, Dong Jik; Lee, In Hee
Abstract: Rationale: Simultaneous occurrence of anti-glomerular basement membrane (anti-GBM) disease and thin basement membrane nephropathy (TBMN), both of which invade the type IV collagen subunits, is very rare. Here, we present the case of a 20-year-old male patient diagnosed with both anti-GBM disease and TBMN upon presenting dyspnea and hemoptysis. Patient concerns: No laboratory abnormalities, except arterial hypoxemia (PaO2 75.4 mmHg) and microscopic hematuria, were present. Chest computed tomography revealed bilateral infiltrations in the lower lung fields; thus, administration of empirical antibiotics was initiated. Gross hemoptysis persisted nonetheless, and bronchoscopy revealed diffuse pulmonary hemorrhage with no endobronchial lesions. Broncho-alveolar lavage excluded bacterial pneumonia, tuberculosis, and fungal infection. Diagnosis: Enzyme-linked immunosorbent assay of his serum was positive for anti-GBM antibody (95.1 U/mL). Human leukocyte antigen (HLA) test was positive for both HLA-DR15/-DR04. Other than diffuse thinning of the GBM (average thickness, 220 nm), index kidney biopsy did not demonstrate any specific abnormalities such as crescent formation. Interventions: Methylprednisolone was administered intravenously for 7 consecutive days (500 mg/day), followed by the daily dose of oral prednisolone (80 mg). Cyclophosphamide was also orally administered every day for 3 months (250 mg/day). Following 6 sessions of plasmapheresis, the anti-GBM antibody in serum became negative. Outcomes: There was no clinical evidence suggesting recurrence of pulmonary hemorrhage or azotemia during hospitalization and 12-month follow-up period. Twelve months after hospital discharge, oral prednisolone was discontinued. Lessons: The patients with concurrent anti-GBM disease and TBMN will have a favorable prognosis after proper therapy. However, further research is needed to elucidate the pathogenesis and long-term outcome of the comorbidity of these 2 diseases.